Indonesian Comprehension Proposition on Malaysian Students of UIN Sunan Ampel Surabaya - Lukman Fahmi; Amiatun Nuryana; Faizah Laela (Ranah: Jurnal Kajian Bahasa, 2024)
In this case, the researcher investigates the students from Kuala Lumpur who study in Da’wa and Communication Faculty UIN Sunan Ampel Surabaya. They have difficulties understanding Indonesian Grammar.  Such as, when they write a scientific papers or academic assignments, papers, and theses.  The factors that make them experience problems in understanding Indonesian are derived from internal and external factors.  Internal factors are in their spirit to learn Indonesian  and External influences have a significant impact on their ability to learn Indonesian verbally and in writing. UIN Sunan Ampel has a BIPA program. This is placeis for learning Indonesian language skills (speaking, writing, reading, and listening) for language speaking. This research applied a type of qualitative descriptive research. It aims to describe, analyze, and provide an accurate systematic description of the communication problems experienced by Kuala Lumpur international students pursuing undergraduate education at UIN Sunan Ampel Surabaya. The research data were obtained from observations and interviews with research subjects. The researcher used a case study for this research approach. This research was conducted on five international students from Kuala Lumpur in semesters 4, and 8 at UIN Sunan Ampel Surabaya, in semesters 6 there are no students from Kuala Lumpur precisely at the Faculty of Da'wah and Communication.  All data collected is analyzed, and then the results are written into a series of sentences in paragraphs. The qualitative descriptive method was applied in this study through observation and interviews. This study found that the understanding of language experienced by Kuala Lumpur. The factors that make them experience problems in understanding Indonesian are derived from internal and external factors.  Internal factors themselves and external influences have a significant impact on Kuala Lumpur students' ability to learn Indonesian verbally and in writing a student lies in understanding written and spoken. AbstrakDalam hal ini, peneliti menyelidiki mahasiswa asal Kuala Lumpur yang belajar di Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya. Mereka kesulitan memahami Tata Bahasa Indonesia.  Misalnya saja ketika mereka menulis karya ilmiah atau tugas akademik, makalah, dan tesis.  Faktor yang membuat mereka mengalami kendala dalam memahami bahasa Indonesia berasal dari faktor internal dan eksternal.  Faktor internal yaitu semangat mereka untuk belajar bahasa Indonesia dan pengaruh Eksternal mempunyai pengaruh yang signifikan terhadap kemampuan mereka dalam belajar bahasa Indonesia lisan dan tulisan. UIN Sunan Ampel mempunyai program BIPA. Tempat ini untuk pembelajaran keterampilan berbahasa Indonesia (berbicara, menulis, membaca, dan mendengarkan) untuk berbicara bahasa.  Dalam penelitian ini menggunakan jenis penelitian deskriptif kualitatif. Bertujuan untuk mendeskripsikan, menganalisis, dan memberikan gambaran sistematis yang akurat mengenai permasalahan komunikasi yang dialami mahasiswa internasional Kuala Lumpur yang menempuh pendidikan sarjana di UIN Sunan Ampel Surabaya. Data penelitian diperoleh dari observasi dan wawancara terhadap subjek penelitian. Peneliti menggunakan studi kasus untuk pendekatan penelitian ini. Penelitian ini dilakukan pada lima mahasiswa internasional asal Kuala Lumpur semester 4, dan 8 di UIN Sunan Ampel Surabaya, pada semester 6 tidak ada mahasiswa asal Kuala Lumpur tepatnya di Fakultas Dakwah dan Komunikasi.   Seluruh data yang terkumpul dianalisis, kemudian hasilnya dituliskan dalam rangkaian kalimat dalam paragraf. Metode deskriptif kualitatif diterapkan dalam penelitian ini melalui observasi dan wawancara. Penelitian ini menemukan bahwa pemahaman bahasa dialami oleh Kuala Lumpur. Faktor yang membuat mereka mengalami kendala dalam memahami bahasa Indonesia berasal dari faktor internal dan eksternal.  Faktor Internal dalam diri sendiri dan Pengaruh Eksternal Eksternal mempunyai pengaruh yang signifikan terhadap kemampuan siswa Kuala Lumpur dalam belajar bahasa Indonesia lisan dan tulisan. Siswa terletak pada pemahaman tulisan dan lisan.